2022
DOI: 10.1080/14999013.2021.1953193
|View full text |Cite
|
Sign up to set email alerts
|

Unidimensionality of the Strengths and Vulnerabilities Scales in the Short-Term Assessment of Risk and Treatability (START)

Abstract: The Short-Term Assessment of Risk and Treatability (START) is a 20-item structured professional judgment instrument for assessing dynamic risk in mental health services. Much of the START research literature examines the relationship between Strengths and Vulnerabilities sub-scale total scores and various adverse outcomes including violence. This assumes that the two sub-scales have the psychometric property of unidimensionality i.e. all the items cluster together as a measure of a single construct. Such assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…By using START as a caring tool for treatment planning and interventions, our results point out items relevant to address to reduce risk of violence. In several studies, this sum is found to have a predictive validity, and we have also found in a previous study that it was a homogeneous construct (Whittington et al, 2022). Of special relevance is that we can describe certain critical factors as more relevant to address in the care planning for reducing risk for future violence.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…By using START as a caring tool for treatment planning and interventions, our results point out items relevant to address to reduce risk of violence. In several studies, this sum is found to have a predictive validity, and we have also found in a previous study that it was a homogeneous construct (Whittington et al, 2022). Of special relevance is that we can describe certain critical factors as more relevant to address in the care planning for reducing risk for future violence.…”
Section: Resultssupporting
confidence: 76%
“…Therefore, using the total sum of vulnerability scores should be regarded as a reasonable measure of future risk, especially risk for violence. Furthermore, it has been noted that the sum of vulnerabilities is a unidimensional construct (Whittington et al, 2022). Subsequently, changes over time in total vulnerability score reflect a change in risk for future violence.…”
mentioning
confidence: 99%
“…Previous research has primarily focused on its validation and predictive ability ( 19 , 20 ). The most recent study focused on summarizing item values as a single concept, primarily for research purposes ( 21 ). To our knowledge, no previous study has highlighted the reduction in mechanical restraint use as an outcome.…”
Section: Introductionmentioning
confidence: 99%
“…To inform the formulation of SREs, the START considers a wide range of items (O'Shea & Dickens, 2014), of which the more frequently studied are 20 dynamic items rated both as protective factors ("strengths") and risk factors ("vulnerabilities"). The START distinguishes itself from other risk assessment instruments by its emphasis on dynamic variables, the inclusion of strengths in the assessment process, and its consideration of understudied outcomes such as substance misuse, self-neglect, unauthorized leave, and victimization (Marriott et al, 2017;Whittington et al, 2022). A youth version was developed and validated: the START adolescent version (START-AV; J. L. Viljoen et al, 2012Viljoen et al, , 2014.…”
mentioning
confidence: 99%